A Diagnostic Pitfall in the Evaluation of CD138-Positive Plasmacytoid Cells in a Fine Needle Aspiration Biopsy. (28th October 2021) - Ali, H; Mai, B; Wahed, A; Nguyen, A; Liu, J; Zhu, H
Abstract: Introduction/Objective: The identification of plasmacytoid cells on rapid assessment leads to a wide range of differential diagnoses. Methods/Case Report: We present a 51-year-old female with a parotid mass and cervical lymphadenopathy. The fine needle aspiration biopsy of the lymph node showed clusters of plasmacytoid cells. Flow cytometric studies showed cells positive for CD19, CD45, CD138 and kappa, but negative for CD38 and lambda. The kappa to lambda ratio was greater than 100. Histological sections showed plasmacytoid cells that were positive for AE1/AE3, S100, and SOX10, weakly positive for CK7 and GATA3, but negative for CD79a, CD45, EMA, p40, p63, and pan-melanoma markers. Kappa and lambda had a 1:1 ratio. Due to the discrepancy between the flow cytometric results and the immunohistochemistry, excision was recommended. The subsequent excision specimen showed classic morphology for myoepithelial carcinoma, plasmacytoid variant. Results (if a Case Study enter NA): NA Conclusion: Myoepithelial carcinomas of the salivary glands are rare neoplasms, and they have various morphologies. The plasmacytoid variant can pose as a diagnostic pitfall. In fine needle aspiration biopsies, carcinoma cells with plasmacytoid morphology can be confused with a plasma cell neoplasm. CD138 is nonspecific marker, and it can be expressed in plasma cells as well as carcinomas. To further complicate matters, pancytokeratin and SOX10 can aberrantly expressed in some plasma cell myelomas. Flow cytometry studies is a valuable tool to define various cell types. However, it can be misleading if it is used as a sole source for interpreting plasmacytoid cells. Epithelial and myoepithelial neoplasms should be considered as differential diagnoses when CD138-positive plasmacytoid cells are encountered. Extended immunohistochemistry panel including multiple epithelial and myoepithelial markers play pivotal role in settling the diagnosis.